Massively parallel sequencing of mitochondrial genome in primary open angle glaucoma identifies somatically acquired mitochondrial mutations in ocular tissue - Vallabh, Neeru Amrita; Lane, Brian; Simpson, David; Fuchs, Marc; Choudhary, Anshoo; Criddle, David; Cheeseman, Robert; Willoughby, Colin (Scientific reports, 2024)
Glaucoma is a sight threatening neurodegenerative condition of the optic nerve head associated with ageing and marked by the loss of retinal ganglion cells. Mitochondrial dysfunction plays a crucial role in the pathogenesis of neurodegeneration in the most prevalent type of glaucoma: primary open angle glaucoma (POAG). All previous mitochondrial genome sequencing studies in POAG analyzed mitochondrial DNA (mtDNA) isolated from peripheral blood leukocytes and have not evaluated cells derived from ocular tissue, which better represent the glaucomatous disease context. In this study, we evaluated mitochondrial genome variation and heteroplasmy using massively parallel sequencing of mtDNA in a cohort of patients with POAG, and in a subset assess the role of somatic mitochondrial genome mutations in disease pathogenesis using paired samples of peripheral blood leukocytes and ocular tissue (Tenon’s ocular fibroblasts). An enrichment of potentially pathogenic nonsynonymous mtDNA variants was identified in Tenon’s ocular fibroblasts from participants with POAG. The absence of oxidative DNA damage and predominance of transition variants support the concept that errors in mtDNA replication represent the predominant mutation mechanism in Tenon’s ocular fibroblasts from patients with POAG. Pathogenic somatic mitochondrial genome mutations were observed in people with POAG. This supports the role of somatic mitochondrial genome variants in the etiology of glaucoma.